ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PEGAWAI (Studi Pada Kantor Sekretariat DPRD Kabupaten Manggarai) - Fitra Mardiana; Rafael Nanggur; Fatimah Riswati (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
Respondents of this study were 35 DPRD employees (as population) and 35 people were taken as the research sample; the sampling method using total sampling. This type of research is explanatory research, using a quantitative approach, data analysis tools using SPSS. The research objectives are: 1) To determine the effect simultaneously on the level of work ability, motivation and level of education on the performance of the secretariat staff of DPRD Manggarai Regency. 2) To determine the effect partially simultaneously on the level of work ability, motivation and level of education on the performance of the secretariat staff of DPRD Manggarai Regency. The results showed that : 1) Simultaneously, the level of work ability, motivation and education level had a positive and significant effect on the performance of the Manggarai Regency DPRD secretariat employees, as evidenced by the calculated F value that was owned was 4.439 with a significant level of 0.02 ( less than 0.05). 2) Partially, the level of work ability, motivation and level of education have a positive and significant effect on the performance of the secretariat staff of the Manggarai Regency DPRD, as evidenced by the t value of each independent variable, namely: the level of work ability has a t value of 1.019 with the level of a significance of 0.001 (less than 0.05); work motivation has a t value of 1.069 with a significance level of 0.02 (less than 0.05); and the level of education has a t value of 2.477 with a significance level of 0.03 (less than 0.05). The level of education has a dominant effect on the performance of the Manggarai Regency DPRD secretariat staff.